Analisis Kinerja Pemerintah Daerah Jawa Tengah Ditinjau Dari Pendapatan Asli Daerah, Belanja Modal, Dana Perimbangan Dan Opini Audit BPK - Alfina Al Marsa Putri; Winarsih (Jurnal Ilmiah Raflesia Akuntansi, 2025)
This research aims to analyze and determine the influence of local own-source revenue on financial performance, to analyze and determine the influence of capital expenditure on financial performance, to analyze and determine the influence of balancing funds on financial performance, and to analyze and determine the audit opinion on financial performance. The population used in this study is the Regional Government Financial Statements for the 2020-2023 fiscal years. The total sample used in this study is 140 samples using the census sampling method. The data was processed using IMB SPSS 26 software. The analytical tool used in this research is multiple linear regression. According to the research findings, local own-source revenue has an influence on financial performance, capital expenditure does not have an influence on financial performance, balancing funds do not have an influence on financial performance, and the audit opinion does not have an influence on financial performance.